1972
DOI: 10.1152/ajplegacy.1972.222.5.1132
|View full text |Cite
|
Sign up to set email alerts
|

Renal autoregulation and renin release during changes in renal perfusion pressure

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
18
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 0 publications
5
18
0
Order By: Relevance
“…Renal vascular resistance increased from 0.36 to 0.61 and 0.95 PRU as renal arterial pressure was raised from 50 to 100 and from 100 to 163 mm Hg. These experiments confirm the previously demonstrated dissociation between renal vascular resistance and renin release (4,5). Figure 2 depicts the mean change in renal blood flow per mean change in renal arterial pressure for groups 1 and 2.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Renal vascular resistance increased from 0.36 to 0.61 and 0.95 PRU as renal arterial pressure was raised from 50 to 100 and from 100 to 163 mm Hg. These experiments confirm the previously demonstrated dissociation between renal vascular resistance and renin release (4,5). Figure 2 depicts the mean change in renal blood flow per mean change in renal arterial pressure for groups 1 and 2.…”
supporting
confidence: 87%
“…Since the kidney is completely isolated, the influence of renal nerve activity is eliminated. In contrast to most other studies of autoregulation (4)(5)(6)(7)(8)(21)(22)(23), this technique allows the examination of the response to a standard pressure stimulus over a uniform pressure range and excludes the possibility that extrarenal factors related to aortic constriction, vagotomy, carotid sinus denervation, or carotid occlusion influence the response.…”
Section: Renin Depletion and Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators (2,20,25) have not observed an increase in renin with decreases in carotid sinus pressure. Lower body suction (application of subatmospheric pressure) was produced by enclosing the lower part of the subject's body caudal to the iliac crests in an airtight chamber (33).…”
mentioning
confidence: 83%
“…16 The above findings can explain the previous divergent observations on the effects of carotid sinus hypotension on the secretion of renin. In two of the three studies in which renin secretion was not influenced by the carotid baroreflex, the vagi were intact and renal perfusion either was not controlled 14 or not controlled in every experiment. 15 In the third study, the dogs were vagotomized but renal arterial pressure was not controlled.…”
Section: Discussionmentioning
confidence: 99%